The notification of administrative acts of singular effects and the right to legal certainty in Chile - Camacho Cépeda, Gladys (Revista de Derecho Público, 2019)
Law No. 19,880 defines the administrative act as an institute endowed with intense attributes, among others, the presumption of legality, mandatory and enforceability vis-à-vis its recipients. These characteristics recognized by the legislator are justified in the vicarial function of the State Administration in the service of the general interest. However, in order to the administrative decision expressed in an administrative act benefits from those attributes, it must comply with essential formalities that the law imposes on it. In this paper one of these formalities is addressed, which is the notification in the event of acts of particular effects. Its connection with the principle of due process is highlighted, configuring a duty of the Administration with significant legal effects. On the other hand, the breach of the duty to notify has important effects both for the administrator and his assets, and for the realization of the purpose sought by the administrative decision.